KEANEKARAGAMAN MAKROFAUNA TANAH DI PERKEBUNAN KOPI DESA BATU KALUNG KECAMATAN MUARA KEMUMU KABUPATEN KEPAHIANG - Pariyanto Pariyanto; Endang Sulaiman; Bahlul Ihdana (Jurnal Biosilampari : Jurnal Biologi, 2020)
This study aims to determine the diversity of existing soil macrofauna at coffee plantations located at Batu Kalung village, Muara Kemumu subdistrict of Kepahiang regency. This research was conducted in February 2018 at the coffee plantations area. The methods used in this research were pitfall-trap and hand sorting. The result of the study at the site found there are 9 orders of macraofauna consisting of 11 families, 13 species, and 188 spesimen.The species found were Heterometrus lepturus, Scolopendrae morsitans, Trigoniulus corallines, Neocurtilla hexadactylla, Gryllus assimilis, Ceuthophilus maculates, Dolichoderus bituberculatus, Componotus carnelus, Blatta germanica, Blattella orientalis, Odontotaenius disjunctus, Ponthoscolex corethurus, and Hirudo medicinalis. The calculation of soil macrofauna index in coffee plantations found a number of 0.942. This indicates that that the level of soil macrofauna diversity at the coffee plantations is low. The highest soil macrofauna diversity index was found on Ponthoscolex corethurus, which is 0.146. In the contrary, the lowest diversity index was found onHeterometrus lepturus species, 0.011. In addition, The average physics-chemical factor of soil at the coffee plantation was obtained that the soil temperature is 280C, soil pH of 5.8, and soil moisture of 67